Adverse reactions associated with perioral rejuvenation using laser, fat and hyaluronic acid: systematic review. Issue 9 (November 2021) - Sayan, A.; Gonen, Z.B.; Ilankovan, V.
Abstract: Perioral rejuvenation is carried out by surgical and non-surgical tools. The common procedures are laser resurfacing and volumanisation using alloplastic fillers or autogenous fat. Nonetheless, any such procedures are associated with complications. To evaluate a concise presentation of complications and safety associated with different perioral rejuvenation treatments including laser ablation, fat grafting and hyaluronic acid injections. A systematic literature review of all the relevant studies and case reports on complications and adverse reactions associated with laser ablation, administration of fillers and fat for the rejuvenation of perioral region. Twelve articles passed the inclusion criteria (as per PRISMA guidelines) and were scrupulously analysed. Four publications evaluated complications associated with laser resurfacing, five were related to filler augmentation and three were related to fat administration. The results concluded that all three aesthetic treatments are associated with mild to moderate complications. Severe complications are rare but can arise. Clinicians should be mindful of possible complications and able to recognise adverse events so that remedies could be executed with minimal delay. Training and supervision are essential components of ensuring provision of safe aesthetic treatment, and lack of regulation is a concern.